Insulin-Like Growth Factor Binding Protein-6 Promotes the Differentiation of Placental Mesenchymal Stem Cells into Skeletal Muscle Independent of Insulin-Like Growth Factor Receptor-1 and Insulin Receptor - Doaa Aboalola; Victor K. M. Han (Hindawi Limited, 2019)
As mesenchymal stem cells (MSCs) are being investigated for regenerative therapies to be used in the clinic, delineating the roles of the IGF system in MSC growth and differentiation, in vitro, is vital in developing these cellular therapies to treat degenerative diseases. Muscle differentiation is a multistep process, starting with commitment to the muscle lineage and ending with the formation of multinucleated fibers. Insulin-like growth factor binding protein-6 (IGFBP-6), relative to other IGFBPs, has high affinity for IGF-2. However, the role of IGFBP-6 in muscle development has not been clearly defined. Our previous studies showed that in vitro extracellular IGFBP-6 increased myogenesis in early stages and could enhance the muscle differentiation process in the absence of IGF-2. In this study, we identified the signal transduction mechanisms of IGFBP-6 on muscle differentiation by placental mesenchymal stem cells (PMSCs). We showed that muscle differentiation required activation of both AKT and MAPK pathways. Interestingly, we demonstrated that IGFBP-6 could compensate for IGF-2 loss and help enhance the muscle differentiation process by triggering predominantly the MAPK pathway independent of activating either IGF-1R or the insulin receptor (IR). These findings indicate the complex interactions between IGFBP-6 and IGFs in PMSC differentiation into the skeletal muscle and that the IGF signaling axis, specifically involving IGFBP-6, is important in muscle differentiation. Moreover, although the major role of IGFBP-6 is IGF-2 inhibition, it is not necessarily the case that IGFBP-6 is the main modulator of IGF-2.